2017
DOI: 10.7717/peerj.3203
|View full text |Cite
|
Sign up to set email alerts
|

Differential transcript profile of inhibitors with potential anti-venom role in the liver of juvenile and adultBothrops jararacasnake

Abstract: BackgroundSnakes belonging to the Bothrops genus are vastly distributed in Central and South America and are responsible for most cases of reported snake bites in Latin America. The clinical manifestations of the envenomation caused by this genus are due to three major activities—proteolytic, hemorrhagic and coagulant—mediated by metalloproteinases, serine proteinases, phospholipases A2 and other toxic compounds present in snake venom. Interestingly, it was observed that snakes are resistant to the toxic effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 63 publications
1
13
1
2
Order By: Relevance
“…After two chromatographic steps, γBjPLI was isolated with a recovery of 1% of the serum proteins applied initially, which was lower than that recovered by purification of γCdcPLI (2.60%) from plasma of Crotalus durissus collineatus , possibly due to methodological differences and biological characteristics [ 34 ]. Variation in the levels of inhibitors of venom components found in snake plasmas is still not well understood, and may be a physiological response of the snakes to repeatedly contact with the venom or be under a genetically programmed control [ 54 ]. It is known that newborns of Clelia clelia (an ophiophagus snake), even without any contact with venom, have antihemorrhagic properties in serum [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After two chromatographic steps, γBjPLI was isolated with a recovery of 1% of the serum proteins applied initially, which was lower than that recovered by purification of γCdcPLI (2.60%) from plasma of Crotalus durissus collineatus , possibly due to methodological differences and biological characteristics [ 34 ]. Variation in the levels of inhibitors of venom components found in snake plasmas is still not well understood, and may be a physiological response of the snakes to repeatedly contact with the venom or be under a genetically programmed control [ 54 ]. It is known that newborns of Clelia clelia (an ophiophagus snake), even without any contact with venom, have antihemorrhagic properties in serum [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, recently, a study described the clear ontogenetic difference of inhibitors expression by qPCR profile analysis, in which γ-PLI had an up-regulation around 30-fold in adults in relation to juvenile of B . jararaca specimens [ 54 ]. Also, Kinkawa et al demonstrated that the gene expression of α-PLI and β-PLI in Gloydius brevicaudus liver is increased by the intramuscular injection of the PLA 2 derived from its own venom [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, several concepts were further established in the 19 th century, including the one that the natural immunity is not species-specific [23] and can be found in other animals, such as several species of opossums, squirrels, mongooses, and hedgehogs [24–27]. This resistance is generally assigned to mutations in the gene encoding the target of the venom toxin, resulting in an insensitive target, and/or to the presence of neutralizing factors in the blood of resistant animals [2830].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, inhibitors from B . jararaca plasma and serum have been identified, isolated, and characterized, including phospholipase A 2 inhibitors (PLIs) [33], a thrombin inhibitor that also binds to thrombin-like venom toxins [34,35], and a metalloproteinase inhibitor (the anti-hemorrhagic factor Bj46a) [30]. It is believed that these molecules play an important physiologic role in the protection mechanism against self-envenomation and envenomation by other snake species.…”
Section: Introductionmentioning
confidence: 99%
“…Second, resistance gene sequences are likely to show high levels of nonsynonymous variants among the different populations due to reciprocal population‐specific coevolutionary interactions with venom proteins in rattlesnakes (Feldman et al, 2009; Jansa & Voss, 2011). Third, we would also expect venom resistance proteins to show high levels of transcription in the liver, as it is a center for detoxification and secretion of serum proteins (Gomes et al, 2017; Kalsheker, 1989; Rocha et al, 2002). For example, α‐1‐antitrypsin was shown to be under positive selection (Gibbs et al, 2020) and is a protease inhibitor that is transcribed in the liver (Guttman et al, 2015; Kalsheker, 1989).…”
Section: Introductionmentioning
confidence: 99%